Effects of melatonin and Vitamin E on oxidative-antioxidative status in rats exposed to irradiation - Yilmaz, Seval; Yilmaz, Erhan (Elsevier Ireland Ltd, 2006)
Bone marrow is known to be particularly susceptible to radiation. In this study, the effects of treatment with Vitamin E and melatonin and irradiation-induced lipid peroxidation and its association with antioxidant enzymes in the total bone (bone and bone marrow) and skeletal muscle of rats subjected to total body irradiation was investigated. Wistar-Albino rats were intraperitoneally treated with 100 mg/kg Vitamin E or melatonin before exposure to 720 cGy irradiation. Control, irradiation, Vitamin E plus irradiation, melatonin plus irradiation groups were sacrificed by decapitation under ether anaesthesia on the 10th day after irradiation exposure. Application of total body irradiation elevated malondialdehyde (MDA) levels in rat skeletal muscle (p < 0.001), but glutathione peroxidase (GSH-Px) and catalase activities remained unchanged. Application of Vitamin E with irradiation or melatonin decreased the MDA levels in skeletal muscle (p < 0.01), but did not affect the GSH-Px and catalase activity. MDA levels were found elevated in total bone (p < 0.001), GSH-Px activity decreased (p < 0.001) and catalase activity remained unchanged in the group treated with irradiation. Application of Vitamin E with irradiation increased the GSH-Px activity in total bone (p < 0.01), but the activity of MDA and catalase remained unchanged. Treatment of the animals with melatonin concurrent with total body irradiation reduced the degree of lipid peroxidation and elevation in antioxidant enzymes in total bone (p < 0.01). We conclude that melatonin may protect the total bone from the damaging effects of irradiation exposure, and its actions protect total bone from oxidative stress. However, protective effects of Vitamin E were not observed in this study. (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: lipid peroxidation; antioxidant enzymes; melatonin; vitamin E; irradiation